The steepness of the rising branch of adhesive characteristics between wheel and rail - Lata, Michael; Čáp, Jaroslav (Transport, 2010)
The article describes the limiting parameters of the rising branch of adhesive characteristics. Attention is paid to the actual results of experimental research conducted by the authors. A summary of the obtained knowledge is made. In addition, a test stand of tram wheels driven by the synchronous motor and the carried out experiments are described. A comparison of the achieved results is drawn. First published online: 27 Oct 2010